2020
DOI: 10.5551/jat.50674
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA MEG3 Promotes Apoptosis of Vascular Cells and is Associated with Poor Prognosis in Ischemic Stroke

Abstract: Aim: This study focused on the expression pattern of long non-coding RNA maternally expressed gene 3 (MEG3) and its value in ischemic stroke (IS). Methods:The expression pattern and the roles of MEG3 in the development of IS were explored in mice IS model and human brain microvascular endothelial cells (hBMECs). A case-control study, including 215 IS patients and 153 controls, was also conducted to investigate its prognostic value. Results:In vivo study showed that MEG3 increased significantly in the IS group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Another case study was conducted to investigate the relationship between LncRNA MEG3 and prognostic value. MEG3 was upregulated in IS patients, positively associated with the NIHSS score, and negatively related to the prognosis of IS patients ( Wang M. et al, 2020 ). Thus, MEG3 is a potential marker for diagnosis and prognosis.…”
Section: Lncrnas As Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…Another case study was conducted to investigate the relationship between LncRNA MEG3 and prognostic value. MEG3 was upregulated in IS patients, positively associated with the NIHSS score, and negatively related to the prognosis of IS patients ( Wang M. et al, 2020 ). Thus, MEG3 is a potential marker for diagnosis and prognosis.…”
Section: Lncrnas As Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…More importantly, the risk of death was higher in high MIAT expression group compared with the patients with low MIAT expression, in whom better prognosis and survival rate were observed (Zhu et al, 2018 ). In consistence with these findings, Wang et al ( 2020 ) also suggested that MEG3 expression was associated with poor prognosis in patients with ischemic stroke. The risk of death was increased in high MEG3 expression group compared with the control.…”
Section: Lncrnas As Novel Diagnostic and Prognostics Biomarkers For Imentioning
confidence: 65%
“…They were previously considered as “junk” in the mammal genome but now are found to function as a transcriptional regulator or post-transcriptional regulator: in the former, lncRNA combines with chromosomes and modifies the gene expression ( Ulitsky and Bartel, 2013 ), whereas in the latter, lncRNA can either directly impact the gene expression by regulating the degradation of genes or works as competing endogenous RNA (ceRNA) and sponge-specific miRNAs, thus indirectly regulating the gene expression ( Bao et al, 2018 ; Gong et al, 2020 ). Recently, aberrant expression of lncRNA has been reported to correlate with the onset, progression, and prognosis of acute ischemic stroke (AIS) ( Bai et al, 2014 ; Feng et al, 2019 ; Li et al, 2020a ; Wang et al, 2020a ; Fu et al, 2021 ); thus they are potential candidates for stroke diagnosis. Meanwhile, the mechanism of stroke involves a series of complicated processes, including energy depletion, ion imbalance, glutamate and free radical release, calcium channel dysfunction, inflammatory changes, and apoptosis ( Dirnagl et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%